Adenotonsillectomy improves quality of life in children with sleep-disordered breathing regardless of nocturnal enuresis outcome. Issue 5 (October 2015) - Kovacevic, Larisa; Wolfe-Christensen, Cortney; Lu, Hong; Lulgjuraj, Mark; Abdulhamid, Ibrahim; Thottam, Prasad J.; Madgy, David N.; Lakshmanan, Yegappan
Summary: Background: Nocturnal enuresis (NE) and sleep-disordered breathing (SDB) have both been associated with impaired health-related quality of life (HRQoL). The following were investigated: (1) whether tonsillectomy and/or adenoidectomy (T&A) significantly affect the HRQoL in children with NE and SDB, and 2) differences in HRQoL between children with NE persistence versus resolution post-T&A. Methods: This was a prospective study comparing the HRQoL of children with SDB and NE (study group) pre- and 4 weeks post-T&A, and the HRQoL of children with SDB without NE (control group) (independent t -tests). HRQol was assessed using the Obstructive Sleep Apnea Quality of Life 18 questionnaire (OSAS-18), a validated measure containing five subscales that combine to create a total score. Individual items were scored on a Likert-type scale ranging from 1 (none of the time) to 7 (all of the time). Symptoms of SDB were evaluated using the validated Pediatric Sleep Questionnaire (PSQ). Mixed ANOVA was conducted to evaluate changes in the measures between the wet and dry children post-T&A. Pre- and post-T&A change scores were calculated for both the PSQ and the OSAS-18. Results: There were 30 children in the study group (18 male, mean age 9.07 years, SD 2.19), and 30 age-matched controls (16 male). There were no statistically significant differences between the two groups in regards to OSAS-18 total, PSQ total, BMI, diagnosis of snoring or OSAS on sleep study, or race. Overall, OSAS-18 and PSQ scores significantly improved in all children post-surgery ( p < 0.001; p < 0.001, respectively), with no significant differences between dry and wet children post-T&A. The correlation between the pre- and post-T&A change scores on the OSAS-18 and PSQ was significant ( r (29) = 0.58, p = 0.001), suggesting that a reduction in SDB symptoms post T&A is related to improved HRQoL. Conclusions: T&A significantly improved HRQoL in all children with SDB and NE, regardless of NE outcomes. These findings support recommendations for T&A in children with SDB with or without NE. Table Study group ( N = 30) Scales Pre-T&A Post-T&A P -Value OSAS-18 total score, mean (SD) 64.60 (25.9) 30.87 (13.8) <0.001 PSQ total score, mean (SD) 0.55 (0.1) 0.27 (0.1) <0.001